Intoleransi dan Radikalisme Agama: Konstruk LSM tentang Program Deradikalisasi - Endang Supriadi; Ghufron Ajib; Sugiarso Sugiarso (Fakultas Ilmu Sosial dan Ilmu Politik UIN Walisongo Semarang, 2020)
Reformation-era opened the opportunities for political freedom and the development of religious life among the Islamic community in Indonesia. It can be seen in the strengthening of the identity and the movements of religious groups outside the mainstream religious groups, namely radicalism. Acceptance of different narratives based on religious sentiments is shown in the public space by building a distinction between